IY NONET : bridging the gap "For the Good of" Indigenous youth aging out of care - Brooks, Justin Christopher (2022)
This action-oriented inquiry supports Indigenous youth nineteen to twenty-four who are/will be aging out of the child welfare system in British Columbia, Canada, through research and development of a youth life skills program. Indigenous youth are overrepresented in the child welfare system and have little or no support once they reach the age of majority, nineteen. Community stakeholders and current Indigenous youth were engaged to gather insight to serve this vulnerable population best. The IY NONET program would incorporate life skills, health, education, and employment components to set youth up for success in the greater community. This action-oriented inquiry used Indigenous research methods combined with semi-structured interviews to connect with youth and stakeholders to gather relevant information and strategies. This inquiry identified various recommendations such as establishing a community of practice, promoting land-based learning, and hiring Elders in residence for Delegated Aboriginal Agencies on Vancouver Island.